DEVELOPMENT OF ANDROID-BASED LEARNING MEDIA AND STUDENT LEARNING STYLE VAR MODEL - Khoiril Nurman Haqim; Ayub Budhi Amggoro (Automotive Science and Education Journal, 2024)
This development research aims to produce android-based learning media products and VAR model student learning styles on the competency of diagnosing fuel injection system damage for XII TKRO class students of SMK Muhammadiyah 2 Semarang. This research uses the Research and Development (R&D) method with the ADDIE research model (Analysis, Design, Development, Implementation, Evaluation). The research design used Two Group Pretest-Posttest Design. The results of the media product validation assessment by three media experts and three material experts received the criteria "Very feasible". The results of the student satisfaction level questionnaire on the learning media products developed received a satisfaction percentage value of 85.71% with the criteria "Very Satisfied". The learning outcomes of experimental class students with learning media products developed were effective enough to improve student learning outcomes with an N-Gain value of 67%.